Proceedings of the III Advanced Ceramics and Applications Conference - Lee, William E.; Gadow, Rainer; Mitic, Vojislav; Obradovic, Nina.; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2016)
This is the Proceedings of III Advanced Ceramics and Applications conference, held in Belgrade, Serbia in 2014. It contains 25 papers on various subjects regarding preparation, characterization and application of advanced ceramic materials.
An Historical Perspective on the Toughness of Ceramics -- Electrical Discharge Machining (EDM) of High Performance Ceramics -- Electronic States and Absorption of Light in a Lemniscate Shaped Quantum Dot Molecule -- Plasma devices and preparing of nonconductive materials -- FAMA - Facility for Modification and Analysis of Materials with Ion Beams -- Magnetic interactions and magnetotransport in Ge1-xTMxTe diluted magnetic semiconductors -- A Method for Simulation of Grain Coarsening Due to Diffusion in Capillary Liquid Bridge -- Electrical characterization of nanostructured ferrite ceramics by using AC impedance spectroscopy -- Piezoceramic Smart Aggregates for Active Monitoring of Reinforced Concrete Structures -- Electrical Characteristics of Nb doped BaTiO3 Ceramics.
Keywords: Materials; Physical chemistry; Surfaces (Physics).; Materials Engineering; Physical Chemistry; Surface and Interface and Thin Film